Atypical patterns of respiratory sinus arrhythmia index an endophenotype for depression - Yaroslavsky, Ilya; Rottenberg, Jonathan; Kovacs, Maria (Development and psychopathology, 2014)
Can atypical patterns of parasympathetic nervous system activity serve as endophenotypes for depression? Using respiratory sinus arrhythmia (RSA) as an index of parasympathetic nervous system function, we examined this question in two studies: one involving mothers with and without depression histories and their offspring (at high and low risk for depression, respectively), and a further study of adolescent sibling pairs concordant and discordant for major depression. In both studies, subjects were exposed to sad mood induction; subjects' RSA was monitored during rest periods and in response to the mood induction. We used Gottesman and Gould's (2003) criteria for an endophenotype and a priori defined “atypical” and “normative” RSA patterns (combinations of resting RSA and RSA reactivity). We found that atypical RSA patterns (a) predicted current depressive episodes and remission status among women with histories of juvenile onset depression and healthy controls, (b) predicted longitudinal trajectories of depressive symptoms among high- and low-risk young offspring, (c) were concordant across mothers and their juvenile offspring, (d) were more prevalent among never-depressed youth at high risk for depression than their low-risk peers, and (e) were more concordant across adolescent sibling pairs in which both versus only one had a history of major depression. Thus, the results support atypical RSA patterns as an endophenotype for depression. Possible mechanisms by which RSA patterns increase depression risk and their genetic contributors are discussed.